Análise de sensibilidade do modelo termoquímico-mecânico para estruturas de concreto massa - Fraga, Igor Azevedo (2018)
Mass concrete structures are characterized by their differentiated behavior due to their high volume of concrete, because given the high consumption of cement they are more vulnerable to cracking due to the elevation of temperature during the reaction of hydration of the cement. Therefore, dude to the exothermic and thermoactivated nature of the hydration reaction, such structures are subject to volume variations, which, when restricted, cause stresses that may lead to cracking of the material. With regard to research using computational simulations, programs have been developed to map the temperature in the concrete solid as well as its transient fields of stresses and deformations, which allows the prevention of cracking, through the establishment of strategies to prevent it. In order to establish the influence of some parameters intrinsic to the material, in this work the construction of a slab of concrete, previously constructed and tested in the laboratory of FURNAS (Goiˆania / GO) will be simulated, using the finite element program DAMTHE implemented in the language Fortran, developed by PEC / COPPE / UFRJ, using experimental data as the starting point for adjustment of the thermochemical-mechanical model, aiming at obtaining a simulation of reference that represents in the most accurate possible way the tests performed and, later, the accomplishment of a sensitivity analysis varying intrinsic parameters of the material: specific heat capacity, energy activation, thermal conductivity and convective heat transfer.